Physical profile of junior and senior amateur boxers - Wilson, D. C.; Ruddock, A. D.; Ranchordas, M. K.; Thompson, S. W. (Journal of Physical Education and Sport, 2020)
Purpose: The purpose of this study was to profile the physiological characteristics of amateur boxers using a battery of tests designed to assess the physiological and physical demands required for performance. Fifteen junior amateur (age 14.9 ± 2.0 years; stature 164 ± 12 cm; body mass 50.9 ± 11.3 kg) and sixteen senior amateur boxers (n = 16; age 20.5 ± 4.0 years; stature 174 ± 9 cm; body mass 65.2 ± 10.7 kg) provided informed consent to participate in the study. Body composition, squat jump (SJ), countermovement jump (CMJ), 5- and 10 m sprint (5SP/10SP), press up (PU), right and left medicine-ball single-arm throws (MBR, MBL), repeated sprint test (RST) and Yo-Yo intermittent recovery test level 1 (YY) were performed. The likelihood (% chance) of between-group differences were assessed using a magnitude based approach, standardised-difference score (Cohen`s d) and 90% confidence intervals [CI]. Linear regression (r) was used to examine the association between variables. Results: Senior boxers outperformed (79 to 99% chance) junior counterparts in PU, YY, CMJ, SJ, 10SP, MBL and MBR tests (d = 0.50 [-0.34 to 1.61]). There were very large (r 0.70) correlations between fat free mass, upper-and lower body lean mass and medicine ball throw distance. There were large correlations (r 0.50 to 0.69) between medicine ball throw distance and CMJ, SJ, PU, 5SP and 10SP. Conclusions: A simple and time-effective test battery was able to differentiate performance between junior and amateur boxers. These assessments could be useful when profiling junior and senior amateur boxers.